2012
DOI: 10.1002/ardp.201100440
|View full text |Cite
|
Sign up to set email alerts
|

Design and One‐Pot and Microwave‐Assisted Synthesis of 2‐Amino/5‐Aryl‐1,3,4‐oxadiazoles Bearing a Benzimidazole Moiety as Antioxidants

Abstract: In this study, two new series of 2-amino-1,3,4-oxadiazoles and 5-aryl-1,3,4-oxadiazoles carrying a benzimidazole moiety were synthesized. The antioxidant properties of these compounds were investigated in vitro by the determination of the microsomal NADPH-dependent inhibition of lipid peroxidation levels (LP), the microsomal ethoxyresorufin O-deethylase activity (EROD), and DPPH radical scavenger effects. Among the tested compounds, 2-[(2-(4-chlorophenyl)-1H-benzo[d]imidazole-1-yl)methyl]-5-(4-fluorophenyl)-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Oxadiazole carrying benzimidazole moiety was synthesized and evaluated their antioxidant properties by the determination of the microsomal NADPH-dependent inhibition of lipid peroxidation levels (LP), the microsomal ethoxyresorufin O-deethylase activity (EROD), and DPPH radical scavenger effects. Among the tested compounds, (102) was found to be the most active compound (113). The structures for benzimidazole derivatives as antioxidant agents are shown in Figure 9.…”
Section: Antioxidant Agentsmentioning
confidence: 99%
“…Oxadiazole carrying benzimidazole moiety was synthesized and evaluated their antioxidant properties by the determination of the microsomal NADPH-dependent inhibition of lipid peroxidation levels (LP), the microsomal ethoxyresorufin O-deethylase activity (EROD), and DPPH radical scavenger effects. Among the tested compounds, (102) was found to be the most active compound (113). The structures for benzimidazole derivatives as antioxidant agents are shown in Figure 9.…”
Section: Antioxidant Agentsmentioning
confidence: 99%
“…A CSD search (Web CSD version 5.37; August 19, 2016; Groom et al, 2016) found eight benzimidazolium structures with substituents at the 1 and 2 positions of the imidazolium ring system (Morozov et al, 2004;Verdan et al, 2009;Chen et al, 2010;Yuasa et al, 2010;Gao et al, 2013;Samsonov et al, 2013;Liu et al, 2014;Kerimov et al, 2012). In these structures, the imidazolium rings generally show two long (in the range 1.36-1.40 Å ) and two short (1.30-1.34 Å ) C-N distances.…”
Section: Database Surveymentioning
confidence: 99%
“…All the final 1,3,4-oxadiazole derivatives caused significant inhibition (77%-95%) of EROD activity. Typically, imine-containing compounds (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) showed better EROD inhibitory effects than 1,3,4-oxadiazoles (5-12). All the compounds except 7…”
Section: In Vitro Antioxidant Activitymentioning
confidence: 99%
“…Cl - (5)(6)(7)(8)(9)(10)(11)(12) and arylmethyleneamino acetamide (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) (Table 1) were performed and their antioxidant properties were investigated (Table 2).…”
mentioning
confidence: 99%